Administrador escolar: especialista ou educador?: uma análise a partir do caso sergipano - Bezerra, Ada Augusta Celestino (1986)
Public school administration in Sergipe has been submitted to the determinations of the structural-historical context of the state which has changed public schools into mere sites for political party maneuvers. The principals of those schools are represented, as a rule, by people arbitrarily chosen by the state government who immerse the students into the ideology of the dominating upper class. In the prevailing hegemony, the role of this ideology has been a reinforcement to the drop-out and selectivity in public schools and a controlling factor in the distribution of elaborate knowledge among children from the lower classes. There is no difference in the acting of those administrators as far as their policies are concerned. Considering public school s from a progressive perspective and because of the general dissatisfaction observed especially in the state public schools in the capital city and the municipal public schools in the interior of the state, it is suggested in this study that, among other steps, the whole formation process of the educator may emphasize the possibility of his being an organizer of collective pedagogical proposals associated with the community democratization movement. And this should be valid from 'licenciaturas' to 'escolas normaiS' and special training programs for non-professional teachers, extrapolating the scope of discussions about a particular 'habilitação' in the 'Curso de Pedagogia'. It is also proposed a union of forces in the civil society to develop an ample process of discussion to be carried out gradually in the communities (local communities, micro-regional communities, and all-state communities) trying to define the guidelines for educational policies in Sergipe. The mediation that is expected from school organizers is the acting of an administration directed to a basic civil right that every citizen in Sergipe deserves: the competent mastery of accumulated social knowledge. This practice will enable school principals to move from the status of traditional intellectuals to that of progressive intellectuals.